Students Environmental Care Character Building at Islamic Junior High School Diniyyah Al-Azhar Muara Bungo - Vitri Yunesa (International Journal of Educational Dynamics, 2019)
ABSTRACT Environmental care character for students is important to be formed, because the environment will affect the existence and benefit of humans. The character Building is through character education at school. Islamic junior high school Diniyyah Al-Azhar Muara Bungo is an educational institution that seeks to familiarize students with caring for the environment. The purpose of this research is to explain students environmental care character building at Islamic Junior High School Diniyyah Al-Azhar Muara Bungo. This study uses a qualitative method. The research informants were selected by purposive sampling and numbered 14 people. Technique of checking the validity of data by data triangulation. Data analysis techniques with interactive models Miles and Huberman. The findings of this research were: (1) through environmental picket activities, (2) provision of facilities that support environmental care activities, and (3) environmental care slogans Keywords: Environmental Care Character, Students, School, Character Education